1997
DOI: 10.1136/ard.56.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the HLA-DRbeta shared epitope on susceptibility to and clinical expression of rheumatoid arthritis in Chilean patients

Abstract: Objective-To analyse the influence of shared epitope positive HLA-DRB1 alleles (QKRAA or QRRAA) ) on rheumatoid arthritis (RA) susceptibility and severity in Chileans, a population that exhibits a weak association with HLA-DR4. Methods-Prevalence of alleles DRB1*01 and DRB1*04 alleles was determined by polymerase chain reaction amplification and sequence specific oligonucleotide hybridisation in 129 RA patients with defined clinical features and in 97 healthy controls. Results-The shared epitope was found in 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
1
13
0
2
Order By: Relevance
“…Thus, in our population RA is linked to HLA-DRB1*04-QRRAA alleles. As previously reported, 5 we observed a gene dosage effect in the association of the SE with RA (Table 3). This was a cross-sectional study in which the sample size as well as the low number of positive patients for extra-articular manifestations precludes an analysis to test the severity with respect to SE.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…Thus, in our population RA is linked to HLA-DRB1*04-QRRAA alleles. As previously reported, 5 we observed a gene dosage effect in the association of the SE with RA (Table 3). This was a cross-sectional study in which the sample size as well as the low number of positive patients for extra-articular manifestations precludes an analysis to test the severity with respect to SE.…”
supporting
confidence: 89%
“…3,4 Few studies of human leukocyte antigen (HLA) and RA have been done in South-Americans. [5][6][7] However, in Colombians, the association of the SE and RA has not been pre- viously investigated. Therefore, we examined the influence of SE on the susceptibility of RA in a northwestern Colombian population (Medellin), whose ancestral origin is more Caucasian with low Amerindian or Negroid contributions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Supporting this hypothesis, a recent study performed in transgenic mice lacking endogenous MHC-II and bearing the human RA-associated alleles HLA-DRB1*0401 or DQA1*0301/DQB1*0302 showed that exposition of HLA-DRB1*0401-bearing mice to cigarette smoke reduces CIA severity, whilst DQA1*0301/DQB1*0302-bearing mice exposed to cigarette smoke exacerbated CIA manifestation 30 . Studies in Chilean RA-patients show high frequency of the HLA-DRB1*0403 allele 31 , which could account for the differences observed.…”
Section: Discussionmentioning
confidence: 88%